Numerical Analysis of a Dental Zirconium Restoration and the Stresses That Occur in Dental Tissues - Rosa Alicia Hernández-Vázquez; Guillermo Urriolagoitia-Sosa; Rodrigo Arturo Marquet-Rivera; Beatriz Romero-Ángeles; Octavio-Alejandro Mastache-Miranda; G. Guillermo Urriolagoitia-Calderón (Applied Bionics and Biomechanics)
When it is about restorative dental materials, aesthetics is traditionally preferred. This has led to the selection of materials very visually similar to the enamel, but unfortunately, their mechanical properties are not similar. This often translates into disadvantages than advantages. In the present work, a comparison is made of the stresses that occur during dental occlusion (dental bit) in a healthy dental organ and those that are generated in a dental organ with a dental zirconium restoration. Numerical simulation was carried out by means of the Finite Element Method, in computational biomodels, from Cone-Beam Tomography, to obtain the stresses generated during dental occlusion. It was found that the normal and von Mises stresses generated are substantially greater in the molar with restoration compared to those produced in the healthy molar. In addition, the normal function of the enamel and dentin to disperse these stresses to prevent them from reaching the pulp is altered. Therefore, it is necessary to analyze the indiscriminate use of this restoration material and consider other aspects, in addition to aesthetics and biocompatibility for the choice of restorative materials such as biomechanical compatibility.